Optimization of Grid-connected PV System for Renewable Energy Utilization in Railways - Sabrina , Zahra; Adam, Kharisma Bani; Sugiana, Ahmad (eProceedings of Engineering, 2025)
The high electricity demand at railway stations is still largely supplied by fossil-based PLN power plants so its contributing to resulting in carbon emissions. To support the energy transition towards the 2060 Net Zero Emission target, utilizing renewable energy is a strategic solution, one of which is through on-grid solar power plants (PLTS). This study analyzes the implementation of an on-grid solar power plant (PLTS) at Padalarang Station by determining the optimal PV system size using MATLAB simulations with input from load data, solar radiation potential, and Indonesian regulations. Economic feasibility was assessed through Net Present Value (NPV), Return on Investment (ROI), and Payback Period (PP). Results show that a 25 kWp PV system with a 25 kW inverter yields an NPV of Rp378,029,480, ROI of 117.76%, and a payback period of 24 years, proving the system technically and economically feasible to support emission reduction and reduce electricity costs at the station. Keywords: Photovoltaic, On-grid, Railway Station, NPV, Renewable Energy